Faktor Pendukung Dan Penghambat Dalam Pelaksanaan Program Pengembangan Industri Rumahan Di Desa Ngadikusuman, Kecamatan Kertek, Kabupaten Wonosobo: Supporting and Inhibiting Factors in the Implementation of the Home Industry Development Program in Ngadikusuman Village, Kertek District, Wonosobo Regency - Karang, Anak Agung Ayu Uttari Kartika Dewi (Journal of Agricultural Social and Business, 2025)
This research aims to assess the supporting and inhibiting factors in the implementation of the Home Industry Development Program. Employing a qualitative approach with a case study design, this study involved informants comprising facilitators and home industry operators in Ngadikusuman Village, representatives from the Wates Economic Creative Power (WECP), and the Coordinating Ministry for Economic Affairs (MoWECP). Data collection methods included semi-structured interviews and a literature review. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings reveal that supporting factors for this program include the limited number of government programs specifically targeting ultra-micro enterprises, the active roles of various stakeholders from the central to the village level, the diverse benefits experienced by home industry operators post-participation, and the effectiveness and targeted nature of equipment assistance, mentoring, and training. Conversely, identified inhibiting factors encompass budget limitations for annual data collection, the low human resource capacity of home industry operators, difficulties in raw material procurement, product changes by some participants, limited collateral and business capital, a lack of discipline among home industry operators in utilizing loan funds, a reluctance among operators to pursue certification independently, and limited understanding of information technology utilization.